Dobrostan psychiczny i antycypacja sukcesu zawodowego a obraz siebie Badania młodych dorosłych - Komsta-Tokarzewska, Karolina (Chowanna, 2024)
B. Fredrickson, creator of the Broaden-and-Build Theory of Positive Emotions, believes that success in life stems from a sense of happiness, and that happiness builds that success. For half a century, research into psychological well-being sought external sources of life satisfaction. The breakthrough came when the consequences of happiness were addressed. For several years, there has been growing empirical evidence for the thesis of measurable, objective benefits of positive emotions. One of them is the aforementioned professional success. Based on the results of empirical research conducted to date on the determinants of professional success, this article attempts to analyse the relationship between a person’s sense of mental well-being and their estimated professional success in the context of the self-image of the respondents (N = 120). The study confirmed the correlational relationships between the controlled variables. The prediction of professional success and the achievement of professional goals are determined by various subjective characteristics. The above analysis refers only to internal factors, which does not undermine the importance of other determinants, including those of a contextual nature.